Family Atmosphere and Self -Concept among High and Low Achieving Students in General Secondary Examination in Al-Jeezah District, Jordan - Alaedein, Jehad Mahmoud; Al Dahamsheh, Ali Mohammed; Al Dahamsheh, Saif Abdullah (Dirasat: Educational Sciences, 2020)
This study aims at examining the relationship between family atmosphere and self-concept among high and low-achieving students in general secondary examination in Al-Jeezah District, Jordan. The descriptive survey method was used on a sample of 100 high- and low-achievement students in the general secondary examination (52 females and 48 males) in Al-Jeezah District. The family atmosphere scale consisting of 48 items distributed on six subscales, and the self-description questionnaire consisting of 64 items distributed on three subscales were applied to them. Their score averages were also obtained in the General Secondary Examination. The results indicated that there were statistically significant differences at the significance level (0.05) between high and low achievers on the family atmosphere scale and self-concept in favor of high achievers, while there were no significant differences on these two scales according to gender. Moreover, results of the multiple regression analysis showed that the two sub-family climate scales: emotional cohesion and intergenerational authority predicted both self-concept and students' grades. The study calls for the need to raise awareness of the importance of the emotional cohesion and authority between generations prevalent in the family atmosphere among students and parents, and to clarify their role in determining the levels of self-concept, achievement, and academic success for students